Analysis of Code Mixing Used by English Teacher in Classroom Intereaction at Second Grade Students of SMA N 1 Lengayang - Reska Julia; Arwemi Arwemi (Journal Cerdas Mahasiswa, 2022)
This study aims to determine the type of code mixing, the type of code mixing used by the teacher, the code mixing function used by the teacher and the reasons for the teacher using code mixing in the teaching and learning process and classroom interaction at SMA N 1 Lengayang. The research methodology used in this study is a qualitative descriptive method by applying a naturalistic design. The subjects of this study were English teachers at SMA N 1 Lengayang. This study uses observation and interviews in collecting data. The results showed that there were three types of code mixing used by English teachers in the teaching and learning process, namely intra sentential code mixing, intra lexical code mixing and involving changes in pronunciation. Intra sentential code mixing is the dominant type used by English teachers in the teaching and learning process, namely 72 utterances including intra sentential code mixing, 12 utterances including intra lexical and 14 utterances including those involving pronunciation changes. And for the function of code mixing, three functions were found, namely topics, switching to affective functions, and linguistic constraints. Meanwhile, the reason teachers use code mixing in the teaching and learning process is to change the topic of discussion, to approach students and improve students' habits in using English.